Desert hedgehog is a negative regulator of CD44-CD25+ double negative T lymphocytes developmental stage in thymic differentiation - Kariuki, Stephen M. (International Journal of Research in Medical Sciences, 2018)
Background: The process of thymic proliferation and differentiation in mammals is indispensable. The role of hedgehog family of proteins has been extensively studied in the recent past years. Specifically, scientists have carried out substantial amount of work on Sonic hedgehog (Shh) and Indian hedgehog (Ihh) and published on their roles on either T-cell development or peripheral T-cell activation. However, the role of Desert hedgehog (Dhh) the third member of the hedgehog family of proteins, in T-cell development has not been clearly understood. In this work, we aimed to investigate the role of Desert hedgehog in thymic differentiation, particularly in the double negative T cell developmental stages. Methods: Thymuses of three Dhh-/- mice, three Dhh+/- and three Dhh+/+ were obtained by killing the mice using A prepared suspension of cells was analyzed by a three-color flow Cytometry and the acquired data analyzed using flow jo, a tree star software for flow cytometry data analysis. To establish the statistical significance of the findings, data was subjected to student t-test and significance reported at critical p-value of 0.05. Results: The total number of thymic cells was found to be higher in Dhh KO mice relative to the WT control. Analysis of thymic subsets using flow cytometry showed that double negative CD4-CD8- thymocytes were found to be relatively higher in Dhh-/- mice compared to Dhh+/+ control. In particular the percentage representation of CD44-CD25+ DN3 thymocytes were significantly higher (p=0.03) in Dhh KO mice relative to the WT controls. Conclusions: The findings of this study suggest that Dhh signal could be a negative regulator during early thymic differentiation. The data shown here is representative of three separate experiments. To get much clearer and replicative findings, these experiments can be repeated with a much larger sample size.